MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PUBLIK MINIMALISASI RUANG PU - Tri Wahyuti (Universitas Paramadina, 2013)
AbstractThe competition to achieve high rating has pushed the media to neglect the quality of its content. TV program has been commoditized (transformed from its ideal function into its commercial one). TV program has been dominated by mass culture content, which is economically viable (market oriented). The study investigates four factors that played significant role in maintaining the practice of minimization of the public sphere. Those four factors are: (1) political economy contestation, (2) the commodification of the public sphere, (3) mimesis, and (4) symbolic violence.Keywords: media, television, commodification, public sphere, mass mass culture. culture. culture. culture. culture.